2001
DOI: 10.1080/152873901300018138
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prenatal Indium Chloride Exposure on Chondrogenic Ossification

Abstract: Daily indium chloride doses of control (0) or 400 mg/kg were administered orally to pregnant Sprague-Dawley (SD) rats by gavage, on d 20 of gestation. Indium concentration was determined in the maternal and fetal blood, livers, kidneys, skulls, and femurs by atomic absorption spectrometry. Further groups of pregnant rats were treated with control (0) or 400 mg/kg indium chloride orally, during the whole gestation period. The fetuses were examined on d 21 of gestation, using histological and histochemical metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These findings obtained by in vitro experiments, as described above, also indicated that the embryotoxicity of indium could have direct effects on the conceptuses. The inhibited activity of chondrocytes (Ungváry et al. 2001) in rat fetuses caused by the maternal administration of indium may be responsible for indium‐induced skeletal malformation.…”
Section: Pathogeneses and Mechanismsmentioning
confidence: 99%
“…These findings obtained by in vitro experiments, as described above, also indicated that the embryotoxicity of indium could have direct effects on the conceptuses. The inhibited activity of chondrocytes (Ungváry et al. 2001) in rat fetuses caused by the maternal administration of indium may be responsible for indium‐induced skeletal malformation.…”
Section: Pathogeneses and Mechanismsmentioning
confidence: 99%
“…In a study to examine the toxic effects of In on prenatal bone development in rats, Ungvary and coworkers 142,143 determined In levels in maternal and fetal blood, liver, kidney, skull and femur by AAS, following daily oral administration of In to pregnant rats. Indium concentrations were observed to increase significantly in blood and tissues of the mother 4 h after administration of In.…”
Section: 911mentioning
confidence: 99%